Simple One-Pot Synthesis of Sulfonic-Acid-Functionalized Silica for Effective Catalytic Esterification of Levulinic Acid - Desinta Dwi Ristiana; Suyanta Suyanta; Nuryono Nuryono (Indonesian Journal of Chemistry, 2022)
Silica functionalized with sulfonic acid catalyst (SiO2−SO3H) was synthesized through a one-pot method and evaluated as the catalyst material for esterification of levulinic acid in an excess amount of ethanol. Sodium silicate solution was used as the silica source, and then a silane coupling agent, namely GPTMS, was used to incorporate the sulfonic group of 2-aminoethanesulfonic acid (AS) into the silica. Functionalization of AS using GPTMS in the slightly acidic condition has been successfully carried out based on the characterization with FTIR, SEM-EDX, and TGA measurements. Catalyst with the AS to SiO2 molar ratio of 5:6 (SiO2−SO3H(5)) showed the highest acid content (1.02 mmol g–1) and the highest conversion of levulinic acid (70%). The reaction followed pseudo-first-order with the rate constant of 0.00414 min–1. Catalyst material was regenerated by washing with alcohol and water, and the catalyst material can be reused at least for 3 cycles. From this study, the SiO2−SO3H produced from a green process is an effective catalyst to produce esters used in fuel additives.